LITERARY EDUCATION IS AN IMPORTANT FACTOR IN THE DEVELOPMENT OF STUDENTS INTELLECTUAL POTENTIAL - Faizullaeva Gulchehra Sharipboevna (International Journal of Innovations in Engineering Research and Technology, 2021)
The article reveals the development of students' intellectual potential through the teaching of literature in general secondary education, the integration of content in literary education and its role in education